Cultivation of Pleurotus eryngii (DC. ex FR.) quel. on agricultural wastes - Akydz, Mehmet; Yildiz, Abdunnasir (Univ Philippines Los Banos, 2007)
This study investigated the possible use of local agricultural wastes for the cultivation of Pleurotus eryngii (DC. ex Fr.);Quel. For the propagation of the main culture, 2.0 % malt extract agar (MEA) was used whereas wheat grains were used for the propagation of spawn. For the formation of basidiocarp, mixtures of wheat-cotton straw (WC), wheat-millet straw (WM) and wheat straw (W) were used as culture media. Three types of compost were prepared, consisting of a mixture of straws - W, WC (1:1) and WM (1:1). The three compost types were also supplemented with 15 % rice bran (RB). The shortest mycelium-growing period was 15 d on the average in wheat-cotton straw and the longest mycelium-growing period was 27 d in wheat-millet straw. The shortest period for the formation of primordium was 42 d on the average in wheat-cotton straw with peat soil or casing soil (CS) and the longest period was 58 d in wheat straw and in wheat-millet straw without casing soil. The longest period for the formation of the second primordium was 62 d in wheat-millet straw with casing soil. The shortest harvest period was 53 d on the average in wheat-cotton straw with casing soil, while the total harvest period was 72 d on the average in wheat-millet straw with casing soil. The highest biological efficiency (BE) was 73 % in wheat-cotton straw with casing soil, and the lowest BE was 50 % in wheat-millet straw with casing soil. The lowest average yield per 100 g of material (70 % moisture) was 15.0 g in wheat-millet straw with casing soil, while the highest yield was 22.0 g in wheat-cotton straw with casing soil. Based on the results, various local agricultural wastes can be used for the cultivation of Pleurotus eryngii.
Keywords: agricultural wastes; cultivation; harvest; Pleurotus eryngii; yield